Weak solution to evolution problems of harmonic maps from noncompact manifolds - A. Tachikawa (Rendiconti di Matematica e delle Sue Applicazioni, 1999)
In this paper we construct a weak solution for the heat-type equation of harmonic maps from a noncompact manifold into a sphere using the so-called minimizing movement method with the aid of the relative energy.